2017
DOI: 10.3802/jgo.2017.28.e75
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated serum microRNA-101 is associated with aggressive progression and poor prognosis of cervical cancer

Abstract: ObjectiveMicroRNAs (miRNAs) play a vital role in pathogenesis and progression of many cancers, including cervical cancer. However, importance of serum level of miR-101 in cervical cancer has rarely been studied. In the present study, clinical significance and prognostic value of serum miR-101 for cervical cancer was investigated.MethodsAssociation between miR-101 level in cervical cancer tissues and prognosis of patients was analyzed by using data retrieved from The Cancer Genome Atlas (TCGA) database, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Lin et al reported miR-101 upregulation was mostly correlated to significant decreased cellular motility of cervical cancer [ 32 ]. Also, miR-101 downregulation was found in patients with cervical lymph node metastasis and associated with shortened survival time [ 33 ]. In bladder transitional cell carcinoma, low miR-101 expression predicted worse prognosis of patients, and had strong association with the presence of advanced tumor stage and lymph node metastasis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al reported miR-101 upregulation was mostly correlated to significant decreased cellular motility of cervical cancer [ 32 ]. Also, miR-101 downregulation was found in patients with cervical lymph node metastasis and associated with shortened survival time [ 33 ]. In bladder transitional cell carcinoma, low miR-101 expression predicted worse prognosis of patients, and had strong association with the presence of advanced tumor stage and lymph node metastasis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-155 upregulation was an independent prognostic indicator of overall survival for cervical cancer [ 11 ]. Downregulated serum level of miR-101 was an independent predictor of the unfavorable prognosis of cervical cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In association with CIN2-3 and cervical carcinoma, several further miRNAs showing dysregulated expression have been reported, such as miR-218, 29a, −101, −140-5p [40][41][42][43][44]. In the study of Gocze et al (2015), progressively increased expression of miR-27a was demonstrated in CIN2-3 as compared to CIN1 and in squamous cell carcinoma (SCC) as compared to CIN2-3, while the levels of miR-34a were found to be lower in CIN2-3 when compared to CIN1 and in SCC in comparison to CIN2-3.…”
Section: Discussionmentioning
confidence: 99%